Balancing water saving, market attractiveness, and pollution control in crop spatial planting structure planning of arid regions - Longbin Hao; Shouhong Zhang; Fan Zhang; Yufei Ren; Xinyu Zhang; Jing Yan (Agricultural Water Management)
In arid regions, agricultural production and ecological health heavily depend on limited water resources, necessitating the implementation of additional water-saving measures to promote sustainable development. Crop spatial planting structure optimization, as an effective water-saving measure, has been widely utilized to enhance water-use efficiency by aligning the supply and demand of different crops. Besides water-saving benefits, crop planting also offers advantages in terms of market proximity and pollution control. Therefore, this study endeavors to integrate the Von Thunen's agricultural location theory, an agricultural non-point source pollution model, and 0–1 integer multi-objective programming into a unified framework to optimize crop spatial planting structure in arid regions. This approach is applied to a case study in the middle reaches of the Heihe River in northwest China. Results indicate that: (1) The grid-based 0–1 integer multi-objective approach can effectively make tradeoff among market attractiveness, pollution control, and crop suitability for crop planting structure planning in arid regions. (2) Optimal crop planting structure can increase agricultural planting profits by 4.679 billion CNY, while reduces system agricultural non-point source pollution and total water allocation by 34.72 % and 10.19 %, respectively. (3) The multi-objective approach shows better performance than single-objective models by comparing the Synthetic Degree (SD), Sustainability Index (SI), and Approximation Degree (AD). The advantages and successful application of proposed approach indicate that it is universality and effectiveness in addressing agricultural resource management issues in arid regions.